Политиките на правда и внатрешни работи во контекст на јакнењето на безбедноста, правдата и слободното движење на луѓе низ внатрешниот пазар на ЕУ - Лазовски, Владо (Економски факултет, УКИМ, Скопје, 2015)
Policies of Justice and Home Affairs of the European Union are closely correlated with the strengthening of the security of Member States of the Union, Justice, and the free movement of people across the internal market. Some of the important segments in which we will focus in this doctoral dissertation and the individual segments of the policies of justice and home affairs, are the fight against drug trafficking, organized crime, terrorism and trafficking, as well as the extent of migration and asylum in the internal market of the European Union. Republic of Macedonia as a candidate country for membership in the European Union aims to make full harmonization and implementation of legislation related to the policies of the Union, hence the policy of justice and home affairs in the direction of meeting the strategic goal of full membership in the European Union.
EU justice and home affairs policies with the justice and free movement of people in the internal market
Докторска дисертација одбранета во 2015 година на Економскиот факултет во Скопје, под менторство на проф. д–р Билјана Секуловска Габер.
Keywords: justice and home affairs, freedom of movement, Schengen, European Union.